fac-[RuCl2(DMSO-S)3(n-butylamine)]: Synthesis, structural characterization and dual catalytic performance - Silva, Tiago B.; Martins, Daniele M.; Gois, Patrik D.S. [UNESP]; Borim, Patrícia; Maia, Pedro I.S.; Carvalho, Valdemiro P. [UNESP]; Lima-Neto, Benedito S. (Elsevier, 2020)
The synthesis, spectroscopic properties and crystal structure of the novel complex fac-[RuCl2(DMSO-S)3(n-butylamine)] (DMSO-S = sulfur-bonded dimethylsulfoxide) have been reported. The coordination environment of the ruthenium atom is best described as a distorted octahedral, where three DMSO ligands occupy one face of the octahedron, while the two chlorido and the amine ligand occupy the other one. The catalytic activity of fac-[RuCl2(DMSO-S)3(n-butylamine)] was probed in two processes, ring-opening metathesis polymerization (ROMP) and atom-transfer radical polymerization (ATRP). The ROMP of norbornene (NBE) was carried out in the presence of ethyl diazoacetate (EDA) for 5 min at 50 °C which afforded yields around 80%. Poly(norbornadiene) was only produced by photoinduced ROMP leading to 27% yield. The catalytic activity for ATRP of methyl methacrylate (MMA) and styrene (St) for 8 h resulted in 88 and 33%, respectively.
Keywords: Ancillary ligand; ATRP; Crystal structure; Dimethylsulfoxide; ROMP; Ruthenium